Scene in René Fauchois' drama Beethoven at the new theater - Unknown:::Creator:::::::::::: (The Theater Magazine)
Magazine illustration for the play about Beethoven by Fauchois with a photo of Rebecca Warren as Bettina and Donald Robertson as Beethoven